The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3126/jmcjms.v4i2.17071
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of radiation risk among employees in selected hospitals of Nepal

Abstract: Background and Objectives:Nepal is facing the problem of safe, effective and quality radiology services due to lack of adequate knowledge towards advance technology in health sector professionals. Therefore, the present study was designed to focus on the knowledge, attitude and practice on radiation among employee in selected hospitals. Material and Methods:This is a descriptive cross-sectional study conducted in among technical and non technical staff that were involved in or come across the radiology departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…Previously, Maharjan has also carried out similar study and resulted adequate knowledge among radiographers and radiography students participated in an annual conference of Nepal Radiological Society (NRS) [20]. Jha et al also concluded average knowledge, poor perception and satisfactory practices of radiation risk among technical and non-technical staff of radiology department and stressed the malpractice of x-radiation imaging [23]. In this present study, the mean radiation awareness was 68.57 % which was adequate.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previously, Maharjan has also carried out similar study and resulted adequate knowledge among radiographers and radiography students participated in an annual conference of Nepal Radiological Society (NRS) [20]. Jha et al also concluded average knowledge, poor perception and satisfactory practices of radiation risk among technical and non-technical staff of radiology department and stressed the malpractice of x-radiation imaging [23]. In this present study, the mean radiation awareness was 68.57 % which was adequate.…”
Section: Discussionsupporting
confidence: 70%
“…Jha et al . also concluded average knowledge, poor perception and satisfactory practices of radiation risk among technical and non-technical staff of radiology department and stressed the malpractice of x-radiation imaging [ 23 ]. In this present study, the mean radiation awareness was 68.57 % which was adequate.…”
Section: Discussionmentioning
confidence: 99%
“…We strongly recommend providing training and organizing workshops and seminars on radiation safety for dental students in the present condition. There is plenty of research work conducted among radiographers, radiography professionals and physicians related to knowledge of radiation protection in Nepal [1][2][3][15][16][17], however, this study might be the first research of its kind to be conducted among dental students.…”
Section: Discussionmentioning
confidence: 98%